2021
DOI: 10.1002/clt2.12007
|View full text |Cite
|
Sign up to set email alerts
|

The value of small airway function parameters and fractional exhaled nitric oxide for predicting positive methacholine challenge test in asthmatics of different ages with FEV1 ≥ 80% predicted

Abstract: Background Small airway function parameters (SAFPs) combined with fractional exhaled nitric oxide (FeNO) can predict a positive methacholine challenge test (MCT) for asthma diagnosis. However, their predictive utility in patients with forced expiratory volume in one second (FEV1) ≥80% predicted within different age ranges remains unclear. This study aimed to assess the utility of SAFPs, alone or combined with FeNO, to predict a positive MCT in patients in two age groups (<55 and ≥55 years) with asthma‐suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In all of these studies, asthma control was intimately related to SAD and clinical phenotypes associated with SAD, and notably the IOS has better associations than spirometry, supporting the importance of using IOS and more modern tools in addition to spirometry. Studies supporting the relationship between asthma control and severity, asthma features, and SAD ( 18 28 , 30 63 ) are summarized in Figure 1 .…”
Section: Association Of Sad With Specific Asthma Phenotypes and Poor ...mentioning
confidence: 99%
“…In all of these studies, asthma control was intimately related to SAD and clinical phenotypes associated with SAD, and notably the IOS has better associations than spirometry, supporting the importance of using IOS and more modern tools in addition to spirometry. Studies supporting the relationship between asthma control and severity, asthma features, and SAD ( 18 28 , 30 63 ) are summarized in Figure 1 .…”
Section: Association Of Sad With Specific Asthma Phenotypes and Poor ...mentioning
confidence: 99%
“…Combining these two values gave an area under the curve (AUC) of 0.865 (95% CI: 0.833-0.893). They observed that the optimal cut-off for predicting a positive methacholine results to be FEF25-75% of less than 74.9% predicted in patients younger than 55 years of age and less than 62.9% in patients > 55 years of age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCT was performed using a nebulizer with methacholine doses, and forced expiratory volume (FEV1) was measured 5 min after each provocation step. Provocative doses that caused a 20% decrease in FEV 1 were recorded as PD 20 [4].…”
Section: Pulmonary Function Test (Pft) and Methacholine Challenge Tes...mentioning
confidence: 99%